2021
DOI: 10.1021/acs.joc.1c02630
|View full text |Cite
|
Sign up to set email alerts
|

Unique Pseudo-Cross-Conjugated Mesomeric Betaines via an Iodate-Promoted Reaction of 3,3-Difluorocyclopropenes, Pyridines, and Anilines

Abstract: A simple method for the synthesis of (E)-3-arylimino-3H-indolizin-4-ium-1-olates by an iodate-promoted multicomponent reaction between 3,3-difluorocyclopropenes, pyridines, and anilines was discovered. The reaction products belong to a limited and underexplored class of pseudo-cross-conjugated heterocyclic mesomeric betaines isoconjugated with odd nonalternant hydrocarbon anions, whose properties were studied. Reversible nucleophilic addition at the C5 position was revealed as their main chemical feature, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…4 Nechaev et al developed a facile multicomponent synthesis of indolizine-derived PCCMB with high level of functional compatibility making possible the preparation of a number of compounds for materials and medicinal chemistry. 5 These have revealed unique molecular packing and structure-property relationships. 6 In 1932, Diels and Alder reported a cascade reaction of pyridine with dimethyl acetylenedicarboxylate (DMAD) to yield two products whose structures could not be established at that time.…”
Section: Introductionmentioning
confidence: 99%
“…4 Nechaev et al developed a facile multicomponent synthesis of indolizine-derived PCCMB with high level of functional compatibility making possible the preparation of a number of compounds for materials and medicinal chemistry. 5 These have revealed unique molecular packing and structure-property relationships. 6 In 1932, Diels and Alder reported a cascade reaction of pyridine with dimethyl acetylenedicarboxylate (DMAD) to yield two products whose structures could not be established at that time.…”
Section: Introductionmentioning
confidence: 99%
“…[30] In 2022 Nechaev I. V. and co-authors reported an iodatepromoted multicomponent reaction between 3,3-difluorocyclopropenes 86, anilines 87 and pyridines 88. [31] The resulted substituted indolizines 89 and 90 could be used as intermediates for further targeted synthesis (Scheme 33). The authors presented a mechanism for the formation of the indolizine bicycle.…”
Section: Synthesis Of Indolizines Based On Pyridine Derivativesmentioning
confidence: 99%
“…Remarkably, this product cannot be obtained from the corresponding 5aminotropolone in the conditions, we earlier developed for anilines. 12 Unexpectedly, another isomer turned out to be not the quinone 10b, but its regioisomer 10c, where the tropolon-4ylimino group was introduced at the C5 position of the indolizine core. Besides, we also isolated PCC HMB D1 as a minor product of the indolizin-1-ol 2 oxidation by the tropoquinone reagent.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Being structurally unique, all these betaines are remarkable for their moderately intensive charge transfer band in visible spectra, and for the negative solvatochromic effect, character-istical for such PCC HMBs. From a chemical point of view, they strongly tend to react with nucleophiles, 12 however, they are also able for protonation, as was illustrated in the example of PCC HMB type-C. Mesomeric betaine type-D (R�Ph, R 1 �H) was first obtained as a single example (9% yield) in 1988 by Potts et al 17 in the reaction of pyridine-2-yl lithium with (chlorocarbonyl)phenylketene, and since then only a little progress on this type of HMBs was reported. 14 Recently synthesized PCC HMBs type-A were found to be unusual regarding prototropic tautomerism: while exocyclic proton (C7−NH) was anticipated to relocate with a formation of an uncharged quinoid tautomer, this did not happen.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation